Penerapan Pembelajaran Tematik Untuk Meningkatkan Pretasi Belajar Bahasa Indonesia Pada Siswa Kelas II SDK Nuamulu - Yohana Nono BS (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
This study aims to improve Indonesian language learning outcomes. How to apply a thematic approach to Indonesian subjects using a thematic learning approach to The type of research used in this research is classroom action research with the research location in SDK Nuamulu with the subjects in this study being Class II students totaling 31 people. The data collection technique used in this study was using a questionnaire. , observation, interviews, documentation, field notes, and tests. Data were analyzed using descriptive qualitative.